3C 17: The BCG of a Galaxy Cluster at z = 0.22 - Madrid, Juan P. (2018)
Gemini Multi Object Spectrograph medium-resolution spectra and photometric data of 39 objects in the field of the radio galaxy 3C 17 are presented. Based on the new data, a previously uncataloged cluster of galaxies is identified at a mean redshift of z = 0.220 ± 0.003, a projected virial radius of 0.37 Mpc, and a velocity dispersion of σ v = 821 ± 171 km s-1. The brightest member of this cluster is 3C 17, with M r = -22.45 mag. The surface brightness profile of 3C 17 is best fit with two components (Exponential + Sérsic) characteristic of brightest cluster galaxies. The spectrum of 3C 17 is dominated by broad emission lines Hα + N[ ii] and Hβ + [O iii]. Analysis of Chandra data shows extended emission around the cluster core that supports the existence of hot gas cospatial with 3C 17. The discovery of a cluster of galaxies around 3C 17 better explains the sharply bent morphology of the radio jet given that it propagates through a dense intracluster medium.